Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1038/nature03337
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ T-cell help controls CD8+ T-cell memory via TRAIL-mediated activation-induced cell death

Abstract: The 'help' provided by CD4+ T lymphocytes during the priming of CD8+ T lymphocytes confers a key feature of immune memory: the capacity for autonomous secondary expansion following re-encounter with antigen. Once primed in the presence of CD4+ T cells, 'helped' CD8+ T cells acquire the ability to undergo a second round of clonal expansion upon restimulation in the absence of T-cell help. 'Helpless' CD8+ T cells that are primed in the absence of CD4+ T cells, in contrast, can mediate effector functions such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
516
3
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 555 publications
(544 citation statements)
references
References 26 publications
24
516
3
1
Order By: Relevance
“…Thus, we conclude that apoptosis was induced in a paracrine manner by membrane-bound TRAIL. This result corresponds to previous publications characterizing the bystander effect of virally expressed TRAIL, 16 or describing that the production of relevant amounts of sTRAIL by mammalian cells involves secretion of sTRAIL from intracellular stores, 38,39 rather than shedding of the extracellular domain of TRAIL present on the plasma membrane. The analysis of TRAIL receptor expression revealed high surface levels of TRAIL-R2 and lower, but still readily detectable levels of TRAIL-R1, at all culture conditions tested.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, we conclude that apoptosis was induced in a paracrine manner by membrane-bound TRAIL. This result corresponds to previous publications characterizing the bystander effect of virally expressed TRAIL, 16 or describing that the production of relevant amounts of sTRAIL by mammalian cells involves secretion of sTRAIL from intracellular stores, 38,39 rather than shedding of the extracellular domain of TRAIL present on the plasma membrane. The analysis of TRAIL receptor expression revealed high surface levels of TRAIL-R2 and lower, but still readily detectable levels of TRAIL-R1, at all culture conditions tested.…”
Section: Discussionsupporting
confidence: 90%
“…Recently, Janssen et al [8] showed that CD8 + T cells that are primed in the absence of CD4 + T cell help commit activation-induced cell death when they reencounter antigen. They found that unlike helped CD8 + memory T cells, these helpless memory CTL synthesize TRAIL upon restimulation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the production of acute effector cytokines and IL-2 are reduced [7]. "Unhelped" CD8 + T cells die upon in vitro re-activation, due to the expression of tumor necrosis factor-related apoptosis-inducing ligand (TRAIL), which is not expressed by "helped" CD8 + memory T cells [8].…”
Section: Introductionmentioning
confidence: 99%
“…CD4 + T cells are thought to provide help for CD8 + T cells, especially in response to non-inflammatory antigens via the regulation of TNF-related apoptosis-inducing ligand (TRAIL) [22]. CD8 + memory T cells generated without appropriate CD4 + help are defective in their abilities to respond in a recall response and undergo activation-induced cell death upon re-stimulation [14,22,23]. As the B cell helper function of CD4 + T cells exhibits age-related defects, it is likely that this defect also has an influence on the generation of functional CD8 memory T cells.…”
Section: Effect Of Age On Cd8 + T-cell-mediated Memorymentioning
confidence: 99%